PENERAPAN METODE BRAINSTORMING DENGAN BANTUAN MEDIA GAMBAR GRAFIS UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS V SD NEGERI 009 PULAU KECAMATAN BANGKINANG KABUPATEN KAMPAR - Fatma Khaulani; Eddy Noviana; Gustimal Witri (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
ABSTRACTThis research was conducted issuing the low learning outcomes on Civics subject by the fifth grader students of SD Negeri 009 Pulau Bangkinang District, Kampar Regency with an average score of 63.40. It was seen that out of 16 students, there were only 7 students who passed the test (43.75%), while the other 9 students (56.25%) did not. The result was established according to the KKM (minumum score) determined by the school which was 75. The students' low performance might occur because of several reasons: (a) the way the presentation of the material delivered by the teacher did not really involve the students activity; (b) the teacher did not use learning media in explaining the learning material; and (c) the teacher applied an approach, model, or method that was less attractive to the students. This study aims at improving the students' achievement in Civics by using brainstorming methods with the help of graphic image media. The research is a classroom action research (CAR) consisting of three cycles with research subjects of grade V students of SDN 009 Pulau Bangkinang District, Kampar Regency. The results showed improvements in each cycle. The score increased from an average score of 62.50 to 69.06 in the first cycle. In the second cycle, the score increased to 75.93 and in the third cycle increased to 80.94. The increase of the score that occurred in the baseline score of  Daily Test I was 10.49%, then 21.49% in the Daily Test II and 29.50% in the Daily Test III. In other words, the brainstorming method with the help of graphic image media can improve the students learning outcomes in Civics subject.